Assessing signatures of selection through variation in linkage disequilibrium between taurine and indicine cattle - O'Brien, Ana M. Perez; Utsunomiya, Yuri T. [UNESP]; Meszaros, Gabor; Bickhart, Derek M.; Liu, George E.; Van Tassell, Curtis P.; Sonstegard, Tad S.; Da Silva, Marcos V. B.; Garcia, José Fernando [UNESP]; Soelkner, Johann (Biomed Central Ltd., 2014)
Background: Signatures of selection are regions in the genome that have been preferentially increased in frequency and fixed in a population because of their functional importance in specific processes. These regions can be detected because of their lower genetic variability and specific regional linkage disequilibrium (LD) patterns.Methods: By comparing the differences in regional LD variation between dairy and beef cattle types, and between indicine and taurine subspecies, we aim at finding signatures of selection for production and adaptation in cattle breeds. The VarLD method was applied to compare the LD variation in the autosomal genome between breeds, including Angus and Brown Swiss, representing taurine breeds, and Nelore and Gir, representing indicine breeds. Genomic regions containing the top 0.01 and 0.1 percentile of signals were characterized using the UMD3.1 Bos taurus genome assembly to identify genes in those regions and compared with previously reported selection signatures and regions with copy number variation.Results: For all comparisons, the top 0.01 and 0.1 percentile included 26 and 165 signals and 17 and 125 genes, respectively, including TECRL, BT.23182 or FPPS, CAST, MYOM1, UVRAG and DNAJA1.Conclusions: The VarLD method is a powerful tool to identify differences in linkage disequilibrium between cattle populations and putative signatures of selection with potential adaptive and productive importance.